Analisis Komprehensif Kesiapan Kedaruratan Dalam Sistem Manajemen Keselamatan dan Kesehatan Kerja di Industri Manufaktur - Amanda Sari, Desi; Salsabila, Tasya; Hasibuan, Abdurrozzaq (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
Indonesia as one of the countries with a manufacturing industry sector that is experiencing rapid development. In Indonesia, there has been a very significant increase in work accidents, up by 55.2% from 2019 to 2020. The manufacturing industry has a very high contribution in work accidents in a company that does not implement procedures in accordance with standards. K3 aims to prevent, reduce, and even eliminate the risk of work accidents (zero accidents). This study uses the literature review method as a systematic method sourced from the 2020–2024 journal published on Google Scholar. The results of a review of articles conducted with several journals show that emergency preparedness in the occupational safety and health management system in the manufacturing industry shows that OSH Management is a very important aspect in the manufacturing industry. Several components in the emergency response system are divided into emergency response management, emergency facilities and infrastructure, and management in the manufacturing industry. An important aspect in the manufacturing industry. Emergency preparedness in OSH management involves risk understanding, emergency planning, employee training, and monitoring and evaluation.